Analisis Mutu (Input Proses Output) Pendidikan di Lembaga Pendidikan MTs Assalam Kota Mataram Nusa Tenggara Barat - Luthfi Zulkarmain (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2021)
The role of the principal in managing an educational institution must be able to think about three important things, namely Input-Process-Output, these three things must be managed optimally to get quality and quality grades. Teachers and students are an important part of educational institutions. So from that the principal needs to streamline the process of all existing programs. The MTs Assalam educational institution, Mataram City, NTB is a relatively new educational institution because it officially became an educational institution legally in 2019, but students and students there have shown enthusiasm and high motivation to learn whether it is in implementing programs implemented in Islamic boarding schools or at schools They are also active in several extra activities such as tahfidz, student council, scouting, silat and recitation, the policy that is implemented is that it requires all students and students to live in the hut and free food and housing fees. This study aims to analyze in depth the quality and quality (input, process, and output) that exist in the MTs Assalam educational institution, Mataram City, West Nusa Tenggara. This research is a qualitative research with a phenomenological research type. The research instruments used were documentation and observation, data analysis used in this study was data reduction, data presentation and data verification. The results showed that the system of quality development process and the quality of students there is by compulsory boarding and following the rules of the boarding school, collaborating with lodges, collaborating with the community, holding recitations for the community, always coordinating with the santri guardians and building a network of partners with offices - government offices.